1986
DOI: 10.1007/bf01290758
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fission fragment nuclear structure on scission configuration in252Cf (S.F.)

Abstract: With the aim of investigating the influence of fragment nuclear structure e.g. shell closure configuration and odd-even nature on the scission configuration, fragment angular momenta have been deduced from the radiochemically determined independent isomeric yield ratios of the fission products ltlPd, 131Te, 133Te, 134I and 13SCs in 252Cf spontaneous fission. The fragments' angular momenta deduced are 8.8_+1.5, 5.8 _+ 1.0, 6.1 _+ 1.1, 11.5 _+ 1.1 and 9.8 __ 1.2h respectively. The angular momenta data from this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
1

Year Published

1988
1988
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 22 publications
(34 reference statements)
3
23
1
Order By: Relevance
“…Measurements of fission fragment angular momenta provide information about the influence of nuclear structure of the fragments on the scission configuration. The correlations between fragment angular momentum with its quadrupole moment [2], deformations [3], odd-even and shell configurations [3 5], excitation energy [5,6] and excitation energy of the fissioning nucleus [7] at the scission have been established qualitatively with the available data.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Measurements of fission fragment angular momenta provide information about the influence of nuclear structure of the fragments on the scission configuration. The correlations between fragment angular momentum with its quadrupole moment [2], deformations [3], odd-even and shell configurations [3 5], excitation energy [5,6] and excitation energy of the fissioning nucleus [7] at the scission have been established qualitatively with the available data.…”
Section: Introductionmentioning
confidence: 99%
“…These data along with the data obtained earlier from this laboratory [3, for 132I and for 134I have been analysed to arrive at the fragment scission point deformations and the correlation between fragment angular momentum and kinetic/excitation energy.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is worth considering that the experimentally determined isomeric yield ratio is noticeably lower for 129 Sb compared to 128 Sn for the nat U(p, f ) reaction and the same for the 232 Th(p, f ) reaction. The higher J rms values of 129 Sb can be related to the odd-Z effect in the angular momentum of the fragment, as it has been observed that fragments with odd-Z are more deformed than the even-Z fragments, resulting in higher J rms [42]. This effect may be caused by the polarization of the even-Z core by the extra unpaired proton, especially in the region of the N = 82 spherical shell, where the deformation energy surface might be more strongly governed by the protons, as explained in Ref.…”
Section: B Results and Discussionmentioning
confidence: 96%
“…The latter can be associated with the neck radius and semimajor axis at a certain deformation of the fission fragment [80]. Thus, assuming equal Coulomb and nuclear forces at the scission point [42], the fragment angular momentum can be related to the deformation via the semimajor axis.…”
Section: A Derivation Of Initial Angular Momentummentioning
confidence: 99%
See 1 more Smart Citation